Recovery from Lesion-Associated Learning Deficits by Fetal Amygdala Transplants. Issue 1 (2002) - Jain, Suman; Mathur, Rashmi; Sharma, Ratna; Nayar, Usha
Abstract : Bilateral lesions of the amygdaloid complex result in elimination or attenuation of the conditioned freezing that is normally seen in the conditioned emotional response (CER) paradigm and the active avoidance (AA) task. We observed the effect of amygdalar tissue transplantation on the ability of lesioned (central nucleus of amygdala, CeA) rats to learn CER and AA. In two groups of adult Wistar rats, sham operation or bilateral lesions of the CeA were produced electrolytically (2mA for 8 sec). In a third group, fetal amygdalar tissue was transplanted at the CeA-lesioned site 2 d postoperatively. All rats were trained on CER and AA from the 6 th postoperative day. In comparison with the shamoperated group, bilaterally CeA-lesioned rats showed a significant (p < 0.001 ) increase in all CER scores, indicating an acquisition deficit. After fetal amygdalar tissue transplantation, the CER scores significantly decreased (p < 0.05 ) when compared with the lesioned group. A significant (p < 0.01 ) decrease in the percentage of avoidance in the AA task occurring after CeA lesion returned to control values after amygdalar tissue transplantation. In conclusion, in CeA-lesioned rats a complete behavioral deficit in learning CER and AA was restored by transplanting fetal amygdalar tissue at the lesioned site.